Surgical injury in the neonatal rat alters the adult pattern of descending modulation from the rostroventral medulla - Walker, Suellen M.; Fitzgerald, Maria; Hathway, Gareth J. (American Association of Anesthesiologists, 2015)
Background: Neonatal pain and injury can alter long-term sensory thresholds. Descending rostroventral medulla (RVM) pathways can inhibit or facilitate spinal nociceptive processing in adulthood. As these pathways undergo significant postnatal maturation, the authors evaluated long-term effects of neonatal surgical injury on RVM descending modulation. Methods: Plantar hind paw or forepaw incisions were performed in anesthetized postnatal day (P)3 Sprague-Dawley rats. Controls received anesthesia only. Hind limb mechanical and thermal withdrawal thresholds were measured to 6 weeks of age (adult). Additional groups received pre- and post-incision sciatic nerve levobupivacaine or saline. Hind paw nociceptive reflex sensitivity was quantified in anesthetized adult rats using biceps femoris electromyography, and the effect of RVM electrical stimulation (5–200 μA) measured as percentage change from baseline. Results: In adult rats with previous neonatal incision (n = 9), all intensities of RVM stimulation decreased hind limb reflex sensitivity, in contrast to the typical bimodal pattern of facilitation and inhibition with increasing RVM stimulus intensity in controls (n = 5) (uninjured vs. neonatally incised, P < 0.001). Neonatal incision of the contralateral hind paw or forepaw also resulted in RVM inhibition of hind paw nociceptive reflexes at all stimulation intensities. Behavioral mechanical threshold (mean ± SEM, 28.1 ± 8 vs. 21.3 ± 1.2 g, P < 0.001) and thermal latency (7.1 ± 0.4 vs. 5.3 ± 0.3 s, P < 0.05) were increased in both hind paws after unilateral neonatal incision. Neonatal perioperative sciatic nerve blockade prevented injury-induced alterations in RVM descending control. Conclusions: Neonatal surgical injury alters the postnatal development of RVM descending control, resulting in a predominance of descending inhibition and generalized reduction in baseline reflex sensitivity. Prevention by local anesthetic blockade highlights the importance of neonatal perioperative analgesia.